Multilingualism and education researchers' pathways and perspectives - Prasad, Gail ca. 20./21. Jh; Auger, Nathalie 1973-; Le Pichon- Vorstman, Emmanuelle 1972- (Cambridge University Press, 2022)
For decades, international researchers and educators have sought to understand how to address cultural and linguistic diversity in education. This book offers the keys to doing so: it brings together short biographies of thirty-six scholars, representing a wide range of universities and countries, to allow them to reflect on their own personal life paths, and how their individual life experiences have led to and informed their research. This approach highlights how theories and concepts have evolved in different contexts, while opening up pedagogical possibilities from diverse backgrounds and enriched by the life experiences of leading researchers in the field. Beyond these questions, the book also explores the dynamic relationships between languages, power and identities, as well as how these relationships raise broader societal issues that permeate both global and local language practices. It is essential reading for students, teacher educators, and researchers interested in the impact of multilingualism on education